2014
DOI: 10.1021/sc500559g
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Regenerated Cellulose Filaments Prepared from Cellulose Carbamate–NaOH/ZnO Aqueous Solution

Abstract: In this work, regenerated cellulose (RC) filaments were successfully spun from cellulose carbamate in a NaOH/ZnO aqueous solution on a pilot scale. The structure and properties of the RC filaments were characterized using SEM, FT-IR, elemental analysis, 13 C NMR, XRD, 2D WAXD, tensile testing, and dye testing. The nitrogen-free and sulfur-free RC filaments exhibited a bright surface and circular cross section. The filaments demonstrated a typical cellulose II crystal structure and a relatively high degree of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 45 publications
0
33
0
1
Order By: Relevance
“…As illustrated in Figure 10, the chemical shifts of C1 (105.2 ppm), C4 (87.8) ppm, C5 (75.0 ppm) and C6 (62.8 ppm) for the both parts are almost the same as those for regenerated cellulose fibers from CC-NaOH/ ZnO solution. 33,34 In a comparison of the dissolved part, the C4 peak of the insoluble was relatively weak. The previous studies revealed thermal treatment of cellulose would lead to decrease of bands associated with hydroxyl and glycosidic groups, especially in the C4 signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As illustrated in Figure 10, the chemical shifts of C1 (105.2 ppm), C4 (87.8) ppm, C5 (75.0 ppm) and C6 (62.8 ppm) for the both parts are almost the same as those for regenerated cellulose fibers from CC-NaOH/ ZnO solution. 33,34 In a comparison of the dissolved part, the C4 peak of the insoluble was relatively weak. The previous studies revealed thermal treatment of cellulose would lead to decrease of bands associated with hydroxyl and glycosidic groups, especially in the C4 signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To confirm the successful modification of cellulose, Fourier Transform Infrared Spectroscopy (FTIR) of the original cellulose and CC with different DS were performed, and the results are shown in Figure 2. The obvious absorption peak at 1715 cm −1 for the CC sample was assigned to the stretching vibration of the carbonyl group of the carbamate [32,33]. This indicated that urea had successfully reacted with cellulose to form CC.…”
Section: Confirmation Of Carbamation Of Cellulosementioning
confidence: 94%
“…8 In addition, these nanoparticles have received a great amount of attention within the scientific community and industry for their electrical, optical, catalytic, antibacterial, and thermal properties. [9][10][11][12][13][14][15][16][17][18] It is generally believed that nanoparticle dispersity is critical to the functionality of nanocomposites, including the UV-blocking capability. 19,20 Therefore, aggregation of nanoparticles may significantly reduce UV-blocking efficiency and functionality.…”
Section: Introductionmentioning
confidence: 99%